The natural history of a genetic subtype of arrhythmogenic right ventricular cardiomyopathy caused by a p.S358L mutation in TMEM43. (19th April 2013) - Hodgkinson, KA; Connors, SP; Merner, N; Haywood, A; Young, T‐L; McKenna, WJ; Gallagher, B; Curtis, F; Bassett, AS; Parfrey, PS
Abstract : To determine the phenotype and natural history of a founder genetic subtype of autosomal dominant arrhythmogenic right ventricular cardiomyopathy (ARVC) caused by a p.S358L mutation in TMEM43 . The age of onset of cardiac symptoms, clinical events and test abnormalities were studied in 412 subjects (258 affected and 154 unaffected), all of which occurred in affected males significantly earlier and more often than unaffected males. Affected males were hospitalized four times more often than affected females (p ≤ 0.0001) and died younger (p ≤ 0.001). The temporal sequence from symptoms onset to death was prolonged in affected females by 1–2 decades. The most prevalent electrocardiogram (ECG) manifestation was poor R wave progression (PRWP), with affected males twice as likely to develop PRWP as affected females (p ≤ 0.05). Left ventricular enlargement (LVE) occurred in 43% of affected subjects, with 11% fulfilling criteria for dilated cardiomyopathy. Ventricular ectopy on Holter monitor was common and occurred early: the most diagnostically useful clinical test. No symptom or test could rule out diagnosis. This ARVC subtype is a sex‐influenced lethal arrhythmogenic cardiomyopathy, with a unique ECG finding, LV dilatation, heart failure and early death, where molecular pre‐symptomatic diagnosis has the greatest clinical utility.